2000
DOI: 10.1046/j.1464-410x.2000.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

The nurse cystoscopist: a feasible option?

Abstract: Objectives To compare the accuracy achieved by a trained urology nurse practitioner (UNP) and consultant urologist in detecting bladder tumours durinḡ exible cystoscopy. Patients and methods Eighty-three patients underwent exible cystoscopy by both the UNP and consultant urologist, each unaware of the other's ®ndings. Before comparing the ®ndings, each declared whether there was tumour or any suspicious lesion requiring biopsy. Results Of 83 patients examined by¯exible cystoscopy, 26 were found to have a tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 8 publications
(9 reference statements)
0
40
0
Order By: Relevance
“…Interestingly, studies have shown that UNPs were able to obtain as accurate results in cystoscopy as consultant urologists [17]. In a study conducted in Sweden, Fagerberg and Nostell demonstrated that competent and well-trained UNPs can deliver a similar flexible cystoscopy service to that usually carried out by consultant urologists [18].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have shown that UNPs were able to obtain as accurate results in cystoscopy as consultant urologists [17]. In a study conducted in Sweden, Fagerberg and Nostell demonstrated that competent and well-trained UNPs can deliver a similar flexible cystoscopy service to that usually carried out by consultant urologists [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are often responsible for any subsequent intravesical therapy and can, therefore, be involved in all aspects of bladder cancer management. Patients respond positively to having a single contact for any ongoing concerns, 23,24 and appreciate telephone calls to follow-up on their progress, discuss their management plan, and offer counselling services. 25 Clinical outcomes have been examined for nurse cystoscopists, with almost complete agreement between the cystoscopy findings of nurses and urologists training in cystoscopy.…”
Section: Competing Interestsmentioning
confidence: 99%
“…25 Clinical outcomes have been examined for nurse cystoscopists, with almost complete agreement between the cystoscopy findings of nurses and urologists training in cystoscopy. 24,26 One concern is that nurses might have a lower threshold for referring patients for general anaesthetic cysto scopy to further investigate any abnormalities identified at surveillance cystoscopy compared with medical staff, potentially increasing the cost of the service. 26 However, the higher referral rate might simply reflect the learning curve of novice nurse cysto scopists, and other audits have reported equivalent referral rates between nurses and urology personnel.…”
Section: Competing Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have suggested that adequately trained urology nurse practitioners can undertake FC as accurately as can a consultant urologist [3]. The benefit from this is only partly realised if any further management rests with the consultant.…”
Section: Introductionmentioning
confidence: 99%